Episodic ataxias in children and adolescents: Clinical findings and suggested diagnostic criteria - Filippopulos, Filipp Maximilian; Schnabel, Lutz; Dunker, Konstanze; Strobl, Ralf; Huppert, Doreen (Frontiers in Neurology, 2022)
Background The main clinical presentation of episodic ataxias (EAs) consists of vertigo and dizziness attacks lasting for minutes to hours with widely varying accompanying symptoms. The differentiation of EA and episodic vertigo/dizziness syndromes in childhood and adolescence such as vestibular migraine (VM) and recurrent vertigo of childhood (RVC) can be challenging. Furthermore, only few prospective studies of children/adolescents with EA are available. Objective This study aims to characterize clinical and instrument-based findings in EA patients under 18 years of age, to delineate the clinical and therapeutic course in EA, and to present potentially new genetic mutations. Furthermore, the study aims to differentiate distinct characteristics between EA, VM, and RVC patients. Methods We prospectively collected clinical and instrument-based data of patients younger than 18 years, who presented at the German Center for Vertigo and Balance Disorders (DSGZ) at the LMU University Hospital in Munich with EA, VM, or RVC between January 2016 and December 2021. All patients underwent a comprehensive evaluation of neurological, ocular-motor, vestibular and cochlear function, including video-oculography with caloric testing, video head impulse test, vestibular evoked myogenic potentials, posturography, and gait analysis. Results Ten patients with EA, 15 with VM, and 15 with RVC were included. In EA the main symptoms were vertigo/dizziness attacks lasting between 5 min and 12 h. Common accompanying symptoms included walking difficulties, paleness, and speech difficulties. Six EA patients had a previously unknown gene mutation. In the interictal interval all EA patients showed distinct ocular-motor deficits. Significant differences between EA, VM, and RVC were found for accompanying symptoms such as speech disturbances and paleness, and for the trigger factor “physical activity”. Furthermore, in the interictal interval significant group differences were observed for different pathological nystagmus types, a saccadic smooth pursuit, and disturbed fixation suppression. Conclusion By combining clinical and ocular-motor characteristics we propose diagnostic criteria that can help to diagnose EA among children/adolescents and identify patients with EA even without distinct genetic findings. Nevertheless, broad genetic testing (e.g., next generation sequencing) in patients fulfilling the diagnostic criteria should be conducted to identify even rare or unknown genetic mutations for EA.